The Analysis of Learning Competency in Intelligent Control of Laying Hens by Delphi Technique - Srinirat, Tanawut; Rakthai, Saksri (Journal of Vocational Education in Agriculture, 2024)
The purpose of this research was to analyze of the learning competency in intelligent control laying hens. The research process was divided into 2 steps: 1) analyzing the controling competency in laying hen from Bachelor of Technology (Continued) curriculum Program in Animal Production Technology and 2) analyzing the controling competency in laying hen by Delphi Technique with focus group meeting and in-depth interview 5 keyperson experted in educational admistration and asking 16 keyperson experted in teaching by a closed-ended questionnaire with a 5-point estimation scale for 2 rounds. The data were analyzed with median and interquartile ranges. The results showed that the experts agreed that bachelor student in Animal Production Technology (Continuing) programme should be ability to control intelligent laying hens at high level in terms of affective domain at organizing level at the high level with the median value was 4 and the range quartile was 1 ,cognitive domain at evaluating level at the high level with the median value was 4 and the range quartile was 1 and psychomotor domain at mechanism level at the highest level the median was 5, the interquartile range was 1.